Design and development of representational fluency test in physics. (April 2020) - Festiana, I; Firman, H; Setiawan, A; Muslim, M
Abstract: The purpose of this research is to design and develop test representational fluency in physics course for electricity topic for students of electrical engineering. The representational fluency test used system Design and Development Research (DDR) with four phase of development consists of analysis, design, development, and evaluation. The test was validation by five expert judgement. The test consists of 20 item multiple choice. After design test and expert review and validation. This research was conducted at the Universities in Lampung and was implemented with 25 participants. The result in this research was the test is valid and reliable to program implementation.